Studi Potensi Ubi-Ubian Spesifik Lokal dan Upaya Pengembangannya Dalam Mendukung Kemandirian Pangan di Provinsi Bengkulu - Asmah Yani; Wayan Rawiniwati (Universitas Sebelas Maret, 2020)
To support food resilience it is felt necessary to do an inventory of any lokal specific plant is cultivated mainly in the form of crop growers of potatoes in order to develop its potential, because if not preserved such commodities are feared will become extinct and the community remains dependent on food rice. The objective of this research was to know the existence and distribution of potential cassava to support community food resilience in Bengkulu Province, know lokal specific cassava cultivation techniques and how much potential land can be developed to support food resilience in Bengkulu Province. This research was conducted at Regency of Rejang Lebong and Regency of Kepahiang, Province of Bengkulu from January-April 2019. The method of this research were observation approach, (interviews using questionnaires, dept interview and Focus Group Discussion (FGD). The selection of sample location research done by purposive sampling with consideration of the potential growth of the plant tubers. The result showed that in Bengkulu turned out for lokal specific crop potential was sweet potatoes. From 10 countries in Bengkulu, sweet potatoes spread across 7 districts namely Seluma, Mukomuko, Kaur, Central Bengkulu, Kepahiang, Lebong and Rejang Lebong. The potential of land that can be developed for the sweet potato cultivation based on the assumption of the existence of land in location of research there were as many as 6,407.0 ha or 0.33% of the land area of Bengkulu province.